Enhancing cross-cultural well-being: a mixed methods study on critical thinking, cultural intelligence, and eudaimonic well-being in arts students’ cultural identity development - Peng, Yue (Frontiers in Psychology, 2024)
This research explores the role of critical thinking and cultural intelligence in psychological well-being through the lens of cultural identity development. The quantitative analysis utilizes various scales to elucidate the correlation between critical thinking beliefs, cultural intelligence, and well-being. The research results show a significant positive correlation between critical thinking, cultural intelligence, and psychological well-being. The qualitative exploration employing NVivo 20.0 uncovers the nuanced interplay between cultural identity, psychological selfhood, and purposebuilding. Themes such as well-being, cultural intelligence, critical thinking, and facing challenges illustrate how individuals navigate obstacles to achieve a meaningful and authentic life. The research findings suggest that cultivating and developing critical thinking and cultural intelligence positively impact individuals' psychological well-being.